Analysis of Funding Sources for PPDB Activities in Budget Management at Public Schools - Nelly Rahmawati Ningsih; Asep Rahmat Kurnia; Syafitri Ningsih; Muhtadin Muhtadin; Yudi Kirmadi; Maman Suryaman (Jurnal Pemberdayaan Masyarakat, 2025)
Effective financial management in public schools plays a crucial role in sustaining educational services, particularly during the implementation of student admissions, which requires efficient and accountable planning and funding. However, the diversity of funding sources and the limited financial management capacity of schools remain persistent challenges. This study aims to describe the funding practices for PPDB and analyze the strategies used by public schools to optimize various financial sources. Employing a descriptive qualitative approach, data were collected using structured questionnaires distributed to principals and treasurers of several public schools. The data were analyzed thematically and presented in visual formats. Findings indicate that the five main funding sources for PPDB activities are BOS (School Operational Support), RKAS (School Budget and Activity Plans), school committee funds, local education office support, and parents' contributions. While BOS remains the most dominant source, schools are also making efforts to diversify funding. The study concludes that multi-source funding requires transparent, collaborative, and adaptive financial governance. This research contributes to the academic discourse by highlighting the need for managerial capacity building and digital-based financial systems in order to strengthen school-level education financing and ensure equity in educational service delivery.